Study Of Fishing Vessel Motion Response At Muara Angke Port - Irvana, Rizky; Manullang, Shanty; Pusaka, Augutinus; Baidhowi, Ahmad Munir (Institut Teknologi Sepuluh Nopember, 2024)
Muara Angke Port, one of Indonesia's busiest fishing hubs, faces significant challenges due to dynamic water conditions and heavy vessel traffic, including waves, currents, tides, and vessel interactions. These conditions impact the motion response of fishing vessels, affecting their stability, maneuverability, and operational safety. This study aims to analyze the motion response of fishing vessels operating, focusing on environmental factors influencing vessel operations. A comprehensive analytical approach is employed, including the panel method for seakeeping analysis. Specific seakeeping criteria for fishing vessels, as proposed by Tello, are applied to assess vessel performance in various sea states. The findings indicate that fishing vessels can operate effectively in sea states with wave heights up to 3 meters, or sea state 5 and below. These results provide valuable insights into how fishing vessels respond to environmental challenges at Muara Angke Port, offering recommendations for improvements in vessel design. The study emphasizes the importance of developing operational strategies to reduce accidents and enhance the sustainability of the fishing sector, while supporting the long-term resilience of Indonesia's fisheries industry